Evaluation of the Policy on Handling Homeless and Beggar by the Bandung City Government: A Study of Regional Regulation Number 4 of 2020 on Poverty Alleviation - Istyawan, Aryohaji (Indonesian Journal of Social Work, 2025)
The Regional Regulation of Bandung City Number 4 of 2020 concerning Poverty Alleviation has notdemonstrated adequate effectiveness in addressing the issues of vagrancy and begging. According to data fromthe Social Service of Bandung City, the number of homeless individuals increased from 148 in 2019 to 948in 2024, while the number of beggars rose from 2,079 to 4,126 during the same period. This fact indicatesthat the approaches used thus far—such as raids, enforcement, and rehabilitation—have not yieldedeffective and optimal outcomes. This study employed a descriptive-qualitative method, collecting data throughinterviews, observations of research subjects and the Dinas Sosial Kota Bandung, as well as documentanalysis of relevant studies. The evaluation results reveal that most beggars and homeless individuals comefrom poor families experiencing educational and economic disparities as well as dysfunctional familyrelationships. Although many have undergone rehabilitation, they often return to the streets due to the lackof sustainable guidance and skill. Furthermore, weak inter-sectoral coordination has made the eradication ofvagrancy and begging less than optimal. This study recommends three inclusive and collaborative policyalternatives to enhance the effectiveness of poverty alleviation, especially the homeless and beggars.